The Influence of Performance Evaluation Satisfaction, Salary Satisfaction, and Supervisor Support on Employee Turnover Intention: The Mediating Role of Work Engagement - Raditriono Raditriono; Hidajat Hendarsjah (Eduvest - Journal of Universal Studies, 2024)
This study investigates the impact of performance appraisal satisfaction, salary satisfaction, and supervisor support on employee turnover intention, with job attachment acting as a mediating variable. Turnover intention refers to the likelihood of employees leaving their current job, which can significantly affect organizational productivity and incur high costs. The research focuses on employees in the food processing industry in Sukoharjo Regency. Using a quantitative survey and cross-sectional method, data were collected from 300 employees through questionnaires and analyzed using Smart PLS 3.2.9 software. The results indicate that performance appraisal satisfaction, salary satisfaction, and supervisor support positively affect job attachment, which in turn negatively influences turnover intention. Job attachment mediates the relationship between performance appraisal satisfaction, salary satisfaction, and supervisor support on turnover intention. These findings contribute to the literature on human resource management and provide practical insights for organizations to enhance employee retention by fostering job attachment through fair performance appraisals, adequate salary, and strong supervisor support.